2015
DOI: 10.5606/archrheumatol.2015.5109
|View full text |Cite
|
Sign up to set email alerts
|

Number of Metabolic Syndrome Risk Factors is Related to Carotid Intima-Media Thickness in Rheumatoid Arthritis Patients

Abstract: Objectives:This study aims to investigate the relationship between carotid intima-media thickness (CIMT) and clinical and metabolic variables in rheumatoid arthritis (RA) patients. Patients and methods: The study included 76 RA patients (18 males, 58 females; mean age 50.1±9.8 years; range 21 to 69 years) and 42 control subjects (11 males, 31 females; mean age 49.2±9.7; range 28 to 66 years). Erythrocyte sedimentation rate, C-reactive protein, and disease activity score were used to assess disease activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In multiple regression analysis, cIMT was independently associated with CRP (p<0.001) and anti-CCP antibodies (p=0.03). 19 Gökmen et al 24 have found that cIMT was positively correlated with the number of metabolic syndrome risk components in RA patients. They have shown positive correlations between cIMT and age, ESR, CRP, and systolic and diastolic blood pressures.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple regression analysis, cIMT was independently associated with CRP (p<0.001) and anti-CCP antibodies (p=0.03). 19 Gökmen et al 24 have found that cIMT was positively correlated with the number of metabolic syndrome risk components in RA patients. They have shown positive correlations between cIMT and age, ESR, CRP, and systolic and diastolic blood pressures.…”
Section: Discussionmentioning
confidence: 99%